Maurice Duruflé : The Man and His Music - Frazier, James E. (Book collections on Project MUSE., 2019)
Biography of the great French organist and composer (1902-86), and the most comprehensive in any language. James E. Frazier traces Durufle's musical training, his studies with Tournemire and Vierne, and his career as an organist, church musician, composer, recitalist, Conservatoire professor, and orchestral musician. Frazier also examines the career and contributions of Durufle's wife, the formidable organist Marie-Madeleine Durufle-Chevalier. Durufle brought the church's unique language of plainsong into a compelling liaison with the secular harmonies of the modern French school (as typified by Debussy, Ravel, and Dukas) in works for his own instrument and in his widely loved masterpiece, the Requiem Op. 9 for soloists, chorus, organ, and orchestra. Drawing on the accounts of those who knew Durufle personally as well as on Frazier's own detailed research, Maurice Durufle offers a broad sketch of this modest and elusive man, widely recognized today for having created some of the greatest works in the organ repertory -- and the masterful Requiem.